Pancreatic Polypeptide but Not Other Members of the Neuropeptide Y Family Shows a Moderate Association With Perceived Anxiety in Obese Men - Schaper, Selina Johanna; Hofmann, Tobias; Wölk, Ellen; Weibert, Elena; Rose, Matthias; Stengel, Andreas (Frontiers in Human Neuroscience, 2020)
Neuropeptide Y (NPY), peptide tyrosine tyrosine (PYY), and pancreatic polypeptide (PP) are important mediators in the bidirectional communication along the gut-brain-axis. Best known for their role in the regulation of appetite and food intake they are considered to play a crucial role in the development of obesity. Additionally, mounting evidence indicates a regulatory function in anxiety, mood and stress resilience with potential sex differences. In the present study, we examined the associations of NPY, PYY, and PP plasma levels with anxiety, depressiveness and perceived stress in obese patients. We analyzed 144 inpatients (90 female, 54 male, BMI mean: 49.4 kg/m2) in a naturalistic treatment setting for obesity and its somatic and mental comorbidities. Fasting blood samples were taken, and patients completed psychometric self-assessment questionnaires (GAD-7, PHQ-9, PSQ-20) within the first week after admission and before discharge. Plasma concentrations of the peptides were measured by ELISA. Women showed significant higher anxiety (GAD-7: 8.13 ± 5.67 vs. 5.93 ± 5.42, p = 0.04) and stress scores (PSQ-20: 52.62 ± 23.5 vs. 41.23 ± 22.53, p = 0.01) than men. In the longitudinal analysis women with a clinically relevant improvement of anxiety (≥ 5 points on GAD-7, p < 0.001) also showed significant improvements in depression (PHQ-9: 38%, p = 0.002) and PSQ-20 scores (23%, p = 0.005) while anxiety-improved male patients only improved in the subscale tension of the PSQ-20 (34%, p = 0.02). In men we observed a positive correlation of PP with anxiety scores (GAD-7: r = 0.41, p = 0.007) and with age (r = 0.49, p = 0.001) on admission while NPY negatively correlated with age (r = -0.38, p = 0.01). In contrast, there were no significant associations (p > 0.05) in female subjects in the cross-sectional as well as in the longitudinal analysis. In conclusion, women suffering from morbid obesity showed greater psychological comorbidity and considerable interactions among them. Despite that we solely observed associations of PP with anxiety and age with NPY and PP in men, suggesting a possible influence of sex hormones on the NPY system. However, improvement of anxiety scores did not lead to significant changes in NPY.